FAILURE MODES AND WEAR INTERRUPTING CONTACTS OF THE CONTACTORS WITH SUPPRESSION OF ARCING OF THE MAIN CONTROLLER ECG -8ZH - Babyak, M. O.; Teterko, O. A. (Science and Transport Progress, 2007)
The kinds of failures which arise while in service, and features of wear process of contacts of the main controller EMK-8G of a.c. electric locomotives are considered in the work. Some results of natural tests of contacts with brazing from different materials are provided.